An Analysis Of Students’ Anxiety Factors In English Speaking Performance: A Descriptive Study At The Second Semester Students Of English Education - J, Ghea Witha Valenthy; Regina, Regina; Rosnija, Eni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
In learning English, the ability to speak English is one of the skills that students need to master, but there are still many students who feel anxious when speaking in front of many people. This study aims (1) to investigate what anxiety factors are faced by second-semester students and (2) to find out the most dominant anxiety factor faced by the students in English speaking performance. The data were collected by using observation and questionnaires. There were 28 students in the second semester of FKIP Universitas Tanjungpura Pontianak 2022 taken as the subject of this research. In this study, the researcher uses qualitative research as the design. There were seven anxiety factors faced by students in English speaking performance. The factors were grammatical issues (72,49%), lack of vocabulary (71,42%), lack of preparation (62,14%), fear of making mistakes (61,18%), classmates (60,47%), lack of confidence (58,47%), and lack of motivation (49,51%). Meanwhile, the dominant anxiety factor faced by the students was grammatical issues. In conclusion, there were various factors of anxiety faced by the students when performing in English.